Has Revenge Become a Justification to Legitimize the Death Penalty? - Andersson, Stefan (2014)
Revenge has played a role in criminal justice systems for thousands of years. From the Code of Hammurabi, to the Bible, to modern Supreme Court jurisprudence, revenge, or “getting even,” has been a consideration in how wrongdoers are punished, especially with respect to the imposition of the death penalty. Historically, revenge has not been viewed as a legitimate justification for punishment under American legal principles. However, in the past year, both the United States Supreme Court and the Department of Justice have signaled that revenge may well have a legitimate role in justifying the death penalty. This Note will explore the development of revenge as a justification for punishment in the American criminal justice system. It will begin by showing that recent remarks from the bench and the Department of Justice signal a willingness to consider the effects of revenge on crime victims. It will then analyze the concept of revenge as part of a criminal justice system and discuss the United States Supreme Court’s historical views on revenge as a justification for the death penalty. Next, this Note will investigate revenge’s role in the Victims’ Rights Movement, specifically how revenge factors into victim impact statements. Finally, this Note ultimately asserts that revenge is not and should not be a goal of the criminal justice system given the public policy implications